Relationship between health costs and inflammatory profile in public health - Rocha, Ana P. R. [UNESP]; Lira, Fábio S. [UNESP]; Bueno, Denise R.; Inoue, Daniela S. [UNESP]; Queiroz, Dayane C. [UNESP]; Codogno, Jamile S. [UNESP] (Bentham Science Publishers, 2019)
Aim: This study aimed to assess whether there is a correlation between metabolic and inflammatory markers and healthcare costs according to body adiposity and habitual physical activity (HPA). Methods: This is a cross-sectional study, where the sample includes men and women aged over 50. Participants underwent evaluations that included the following variables: i) immunometabolic markers, ii) healthcare costs, iii) obesity, iv) habitual physical activity, and v) history of personal illness. Statistical significance was set at values lower than 5% and the software used was BioEstat. Results: The correlation between metabolic and inflammatory markers and healthcare costs demonstrated a positive and significant relationship, adjusted for obesity and HPA, between glucose concentrations and exam costs (r = 0.343, p-value = 0.007) and total cost (r = 261; p-value = 0.043); HOMA index and cost of exams (r = 0.267; pvalue = 0.038); and IL-10 and cost of medical consultation (r = 0.297; p-value = 0.020). Conclusion: Metabolic and inflammatory markers may be related to the costs of consultations and examinations, independent of obesity and HPA.
Keywords: Cytokines; Healthcare cost; Healthcare system; Noncommunicable diseases; Obesity; Physical activities